Gamma‐Ray Detection Using Bi‐Poor Cs2AgBiBr6 Double Perovskite Single Crystals (Advanced Optical Materials 8/2021). Issue 8 (20th April 2021) - Zhang, Zheng; Cao, Da; Huang, Zhengjie; Danilov, Evgeny O.; Chung, Ching‐Chang; Sun, Dali; Yang, Ge
Abstract : Ge Yang and co‐workers (article number 2001575 ) report the gamma energy‐resolving performance of a new class of all‐inorganic and lead‐free Cs2 AgBiBr6 double perovskite single crystals. The authors grow the crystals from Bi‐normal and Bi‐poor precursor solutions, respectively, and demonstrate that tuning the stoichiometry of Cs2 AgBiBr6 could directly affect its electrical pro perties and enable its response to gamma‐ray radiation. These efforts provide a basis for further development of all‐inorganic and environmental‐friendly perovskites‐based gamma‐ray detector materials.